Association of HbA1c Level with Lipid Profiles among Type 2 Diabetic Patients attended at Medical University of Bangladesh (Journal of National Institute of Neurosciences Bangladesh, 2019)
Background: Type 2 diabetic patients are presented with dyslipidemia.Objective: The objective of this study was to see the association between the HbA1c and lipid profiles among the diabetic subjects.Methodology: The cross-sectional study was carried in the Department of Biochemistry at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, Bangladesh on type 2 diabetic individual attending the endocrine OPD of BSMMU. In this study estimation of HbA1c level and lipid profiles in diabetic subjects were performed and was compared the lipid profiles between the controlled (HbA1c 7%) groups.Result: A total number of 95 patients were recruited for this study. The mean age of the respondents was 42.63 ±5.56 years. Female (8.21± 1.88) had lower HbA1c than male (8.42±2.21) in the study. TC: HDL (6.07±1.02:1) and LDL: HDL (3.88±1.58:1) were also higher. Among the study population 30 had good (HbA1c